Concordance of skin test reactivity between indoor inhalant allergens among children with allergic respiratory disease - Prapasri Kulalert; Paskorn Sritipsukho; Sira Nanthapisal; Orapan Poachanukoon (BMC, 2021)
Abstract Background In vitro studies have demonstrated cross-reactivity among indoor allergen proteins in children with allergic respiratory diseases. However, there are only few studies evaluating in vivo response. A skin prick test (SPT) with commercial indoor solutions is widely used in clinical practice. We aimed to evaluate SPT agreement in children with allergic respiratory disease between pairs of common indoor allergens. Methods We reviewed SPT results of children 2 to 18 years old, diagnosed with respiratory allergic disease. Results from house dust mite (Dermatophagoides farinae, Dermatophagoides pteronyssinus), cockroach (Periplaneta americana, Blatella germanica), cat and dog were collected. Sensitization was defined as ≥ 3 mm in wheal diameter. Kappa coefficient (κ) was used to analyze sensitization concordance for each allergen pair. Results The charts of 300 children, 187 (62.33%) males, were reviewed. Mean age was 7.43 ± 3.29 years with 183 (61%), 140 (46.67%), 45 (15%), 30 (10%) sensitizations to house dust mite (HDM), cockroach, cat and dog, respectively. Sensitization concordance between HDM and cockroach was moderate: κ = 0.53 (95% CI: 0.42-0.64). Moderate agreement occurred between dog and cat: κ = 0.41 (95%CI: 0.30-0.52). HDM-sensitized children showed poor concordance with both cat κ = 0.17 (95%CI: 0.09-0.24) and dog κ = 0.09 (95%CI: 0.03-0.14). There was also poor concordance between cockroach-sensitized children to cat κ = 0.19 (95%CI; 0.11-0.28) and dog κ = 0.11 (95%CI; 0.04-0.18). Conclusion We demonstrated moderate agreement of SPT response between HDM and cockroach as well as dog and cat. This may be due to cross-reactivity. Component-resolved diagnosis should be considered in children with co-sensitization of these allergen pairs.